PERPETUATING WOMEN'S SUBORDINATION: Husband-Wife Relation in Pop Fiqh Literature - Warman, Arifki Budia; Zainuddin, Zainuddin; Eficandra, Eficandra; Renie, Elsy; Setiyono, Setiyono (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Popular fiqh literature addresses practical aspects of life. A considerable portion of this literature portrays women within a conservative framework. This research aims to investigate the tendency of spousal relationships as depicted in those popular fiqh literature. Subsequent to cataloging, a random selection of literary samples underwent qualitative content analysis. The findings revealed that popular fiqh literature on the household, especially on marital relations, is dominated by gender biased discourse by placing women only in the domestic realm where their position is inferior. This dominance stems from the authors’ references projecting back to the provisions of classical fiqh, which are gender biased and lack authoritative interpretation of the texts. The presence of this literature is also due to the market demands of the publishing industry. Furthermore, societal understanding dominated by patriarchal ideology contributes significantly to the prevalence of gender-biased popular fiqh literature.[Abstrak: Literatur fiqh populer mengatasi aspek praktis kehidupan. Sebagian besar dari literatur ini menggambarkan perempuan dalam kerangka konservatif. Penelitian ini bertujuan untuk menyelidiki kecenderungan hubungan suami istri seperti yang digambarkan dalam literatur fiqh populer tersebut. Setelah proses katalogisasi, seleksi acak sampel-sampel dianalisis dengan pendekatan konten kualitatif. Hasil temuan menunjukkan bahwa literatur fiqh populer tentang rumah tangga, terutama dalam hubungan pernikahan, didominasi oleh wacana bias gender yang menempatkan perempuan hanya dalam ranah domestik di mana posisi mereka lebih rendah dibanding laki-laki. Dominasi ini berasal dari referensi penulis yang mencerminkan kembali ketentuan fiqh klasik, yang memiliki bias gender dan kurangnya interpretasi otoritatif dari teks-teks tersebut. Kehadiran literatur ini juga karena tuntutan pasar industri penerbitan. Selain itu, pemahaman masyarakat yang didominasi oleh ideologi patriarki turut berkontribusi secara signifikan pada prevalensi literatur fiqh populer yang bersifat bias gender.]